Influence of job design and compensation on employee job satisfaction at PT Dian Megah Indo Perkasa - Afifa Ainun Nur Anisah; Gunawan (Digital Business: Tren Bisnis Masa Depan, 2024)
This research aims to analyze the influence of job design and compensation on employee job satisfaction at PT. Dian Megah Indo Perkasa. The research method used is explanatory survey method with descriptive and verificative approach. Data were collected through questionnaires distributed to 43 employees of PT. Dian Megah Indo Perkasa as respondents using census. Data analysis was performed using multiple linear regression analysis, determination coefficient, and hypothesis testing. The results of the study indicate that job design and compensation have a positive and significant effect on employee job satisfaction, both partially and simultaneously. Job satisfaction is influenced by job design and compensation, while the rest is influenced by other factors. Good job design, including autonomy, task variety, and task significance, as well as fair and competitive compensation, can enhance employee job satisfaction. Therefore, companies are advised to pay attention to job design that matches employees' abilities, involve employees in decision-making, and provide fair and proportional compensation to increase employee job satisfaction, thus supporting overall company productivity and performance.